(untitled) (The Research of Medical Science Review, 2024)
Background: A main risk factor for ischemic stroke is carotid artery stenosis; hence, early identification with non-invasive imaging modalities such carotid Doppler ultrasonic waves is essential to prevent stroke recurrence and guide therapy options. Objectives: To investigate its correlation with demographic and clinical risk variables as well as assess the efficacy of carotid Doppler ultrasonic in identifying notable carotid artery stenosis in patients of ischemic stroke. Methods: We included 221 ischemic stroke patients in this cross-sectional study at Pak Emirates Military Hospital, Rawalpindi, from July 2024 to October 2024. The degree of stenosis in the left and right carotid arteries was measured using carotid Doppler ultrasounds. The right and left arteries were compared in terms of hemodynamic characteristics including end-diastolic velocity (EDV) and peak systolic velocity (PSV). Results: Among 221 patients, 41.6% had either severe (≥70%) or intermediate (50–69%) stenosis. Male gender (p=0.038), older age (p=0.001), hypertension (p=0.013), diabetes (p=0.029), hyperlipidemia (p=0.008) and smoking (p=0.042) all substantially correlated severe stenosis. While EDV was much higher in the right artery (p=0.043), peak systolic velocity did not change appreciably between the right and left arteries (p=0.089). Compared to patients with moderate stenosis, those with severe stenosis had more incidence of ischemic stroke. Conclusion: In stroke patients, carotid doppler ultrasounds are useful instruments for early identification and evaluation of notable carotid artery stenosis. Emphasizing the need of effective management of hypertension, diabetes, and hyperlipidemia to lower the risk of recurrent ischemic episodes and improve clinical outcomes, the study finds strongly linked modifiable risk variables highly connected with severe stenosis.